2017
DOI: 10.1111/luts.12204
|View full text |Cite
|
Sign up to set email alerts
|

A medical device containing purified bovine colostrum (Monurelle Biogel) in the treatment of vulvovaginal atrophy in postmenopausal women: Retrospective analysis of urinary symptoms, sexual function, and quality of life

Abstract: Monurelle Biogel is an effective treatment for VVA in postmenopausal women, improving sexual life, urinary symptoms, and QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Figure 1 represents the Flow Chart of the study selection process. Twenty-four out the 28 studies included the full texts [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], while 4 were available as abstracts only [ 56 , 57 , 58 , 59 ]. The majority of these articles involved participants from Europe ( n = 14; 52%), 6 (22%) from Asia, 3 (11%) from Africa 1 (4%) from America and 3 (11%) from Oceania.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 represents the Flow Chart of the study selection process. Twenty-four out the 28 studies included the full texts [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], while 4 were available as abstracts only [ 56 , 57 , 58 , 59 ]. The majority of these articles involved participants from Europe ( n = 14; 52%), 6 (22%) from Asia, 3 (11%) from Africa 1 (4%) from America and 3 (11%) from Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the papers were classified by publication type (full texts or abstracts), BC administration route (systemic oral or topical) and study population. BC topical application in uro-gynecology [ 33 , 34 , 35 ] ( Table 2 ), BC as dietary supplement in the sporting population [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] ( Table 3 ), BC as dietary supplement in the pediatrics and preterm infants [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ] ( Table 4 ), BC as dietary supplement in the elderly [ 54 ] ( Table 5 ), BC administration in critically ill patients [ 55 ] ( Table 6 ), abstracts [ 56 , 57 , 58 , 59 ] ( Table 7 ) and then a systematic review on BC clinical applications [ 21 ] ( Table 8 ). In Table 9 the risk of bias of the included (full texts) RCTs was reported according to the CCRBT method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 The decision about VVAPs in menopausal women needs special considerations, and one must give priority to conservative management rather than to surgery. 24,25 There should be evidence-based guidelines and algorithms to be followed by practitioners to help in decisions regarding VVAPs. 14,26,27 The authors have suggested the step-by-step approach for the enhancement of awareness about VVAPs in medical education.…”
Section: Discussionmentioning
confidence: 99%